Struktur dan Fungsi Sosial Nyanyian Rakyat (Lullaby) Laloklah Nak Kanduang Masyarakat di Nagari Paninggahan - Winda Oktania Sari; Hasanuddin WS Hasanuddin WS (Lingua Susastra, 2021)
This research was conducted with the aim of describing the structure and social function of the folk song (lullaby) of Laloklah Nak Kanduang community in Nagari Paninggahan, Junjung Sirih District, Solok Regency. This type of research is qualitative with descriptive methods. Data obtained from informants through recording, recording, observation, and direct interviews with informants. Then the data that has been collected is analyzed in the following stages: (1) the data identification stage, (2) the data analysis stage, (3) the discussion stage and the conclusion of the data classification results, (4) the reporting stage. Laloklah Nak Kanduang's song has a structure like that found in poetry, namely physical structure (lines, stanzas, and sounds) and inner structure (patterns of association, patterns of images and emotions as well as themes and messages). Then the social functions, namely three (1) creative functions, (2) enthusiasm, (3) hope and prayer. The oral tradition of humming needs to be preserved, considering that the values contained in chanting are priceless cultural assets.